Pengaruh Keragaman Produk Dan Digital Marketing Terhadap Minat Beli Konsumen Pada Ms Glow Di Kota Langsa - Wahyuni, Rahmi; Lindung Bulan, Tengku Putri; Amilia, Suri (Universitas Labuhanbatu, 2022)
This study aims to determine the effect of product diversity and digital marketing on consumer buying interest at MS GLOW in Langsa City. This study used a sample of 96 respondents who used MS GLOW products in Langsa City. This study uses a quantitative approach obtained by distributing questionnaires using a Likert scale. The method used is multiple linear regression equation, t test, F test and coefficient of determination test. The results of the t test prove that product diversity has a significant effect on buying interest, digital marketing has a significant effect on buying interest at MS GLOW in Langsa City. The results of the F test state that product diversity, and digital marketing have a significant effect on buying interest at MS GLOW in Langsa City. The result of the coefficient of determination test (Adjusted R²) has a value of 0.368 or 36.8% affecting the buying interest of MS GLOW in Langsa City. While 63.2% is influenced by other variables not examined such as price quality, promotion, brand image.